Ballet “Chasing Two Hares” by Yuri Shevchenko: Intertextual and Intermedial Contexts - Zinchenko, Veronika (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
The relevance of research. The ballet “Chasing Two Hares” was first investigated from the point of view of intertextual and intermedia connections. Also, for the first time, the analysis of the musical component of the film "Chasing Two Hares" directed by V. Ivanov and composer B. Gomolyaka has been carried out. The parameters of interaction between the ballet “Chasing Two Hares” and the film of the same name at different levels are derived: plot, genre, intonation and drama. Main objective of the study is to determine the intertextual and intermedia contexts of Y. Shevchenko’s ballet “Chasing Two Hares”. Research methodology. In the article, the following methods of historical and theoretical musicology were used: historical — to clarify the circumstances of the creation of musical works, comparative — to compare the musical series of the film “Chasing Two Hares” and Y. Shevchenko’s ballet, the method of intertextual analysis — to identify the qualitative indicators of connections between different musical texts, the method of genre-intonation analysis — for the detection of immanent intonational specific features of the named opuses. The results and conclusions of the study. The concepts of “intertextuality” and “intermediality” in the context of the genre of ballet are defined. The ballet “Chasing Two Hares” by Y. Shevchenko is analyzed from the point of view of its genre and intonation specifics, intertextual and intermedia connections with the film “Chasing Two Hares” directed by V. Ivanov. The musical component of the film, the author of which was V. Gomolyaka, is considered. The main methods of V. Gomolyaka’s work are determined when he creates intonation characteristics of the main characters of the film (Golokhvostov, Pronya) by means of musical expressiveness. Golokhvostov has two contrasting leit-themes, Pronya — one leit-theme, which undergoes intonation changes at the end of the film. The genre and intonation coordinates of the sound landscape of the city of Kyiv have been determined, which V. Gomolyaka reproduces the motley picture of the city of the late 19th and early 20th centuries (church bells, urban folklore, klezmer music, etc.). The intonation and literary genesis of the ballet “Chasing Two Hares” by Y. Shevchenko has been clarified. The parameters of interaction of the film “Chasing Two Hares” with Y. Shevchenko’s ballet are derived: plot (introduction of the heroine Madame), genre (involving the semantics of genres: waltz, march, song, couplets, etc.), intonation (rethinking of sound models by Y. Shevchenko and ideas of V. Gomolyaka). The intertextual and intermedia connections of Y. Shevchenko’s ballet with other literary texts are traced: M Starytsky’s play “Gentleman lip without teeth, or Chasing Two Hares”, I. Nechuy-Levitsky’s play “On Kozhemyaki” and the film “Chasing Two Hares” directed by V. Ivanov and composer V. Gomolyaka. The individual author’s style of the composer is comprehended from the point of view of work in the genre of ballet.